2020
DOI: 10.3390/e22010104
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Cardiotocographic Signals as A Predictor of Labor

Abstract: Prediction of labor is of extreme importance in obstetric care to allow for preventive measures, assuring that both baby and mother have the best possible care. In this work, the authors studied how important nonlinear parameters (entropy and compression) can be as labor predictors. Linear features retrieved from the SisPorto system for cardiotocogram analysis and nonlinear measures were used to predict labor in a dataset of 1072 antepartum tracings, at between 30 and 35 weeks of gestation. Two groups were def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The number of articles probing the use of non-linear measures to assess the fHR signals analysis has been growing in the past decade. Non-linear analysis has been successfully applied in the study of fetal heart rate with several research objectives, such as fetal maturation or gestational age (197)(198)(199), fetal gender (182,200), labor stages (201,202), cesarean section (51,203), preterm birth (80,204), impact of nuchal cord on antenatal (205), fHR baseline (206), behavioral state (207,208), IUGR (209)(210)(211)(212)(213), hypoxia (128,137,214,215), fetal distress (216)(217)(218), maternal pathologies (219,220), and signal processing (198,(221)(222)(223)(224). Therefore, it is important that the scientific community is aware of the non-linear methods used depending on the research objective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of articles probing the use of non-linear measures to assess the fHR signals analysis has been growing in the past decade. Non-linear analysis has been successfully applied in the study of fetal heart rate with several research objectives, such as fetal maturation or gestational age (197)(198)(199), fetal gender (182,200), labor stages (201,202), cesarean section (51,203), preterm birth (80,204), impact of nuchal cord on antenatal (205), fHR baseline (206), behavioral state (207,208), IUGR (209)(210)(211)(212)(213), hypoxia (128,137,214,215), fetal distress (216)(217)(218), maternal pathologies (219,220), and signal processing (198,(221)(222)(223)(224). Therefore, it is important that the scientific community is aware of the non-linear methods used depending on the research objective.…”
Section: Discussionmentioning
confidence: 99%
“…The indices presented in this review are closely related to fetal heart variability. For instance, in ( 199 ) the authors showed that the complexity indices correlate highly with abnormal STV. In ( 143 ) the authors also report correlations between the complexity indices ranging from 0.53 to 0.78.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that future studies may involve the utilization of PhEn as a potential biomarker for evaluating the physiological onset of human labor or even analyzing preterm labor in clinical practice. Recent relevant studies suggest that nonlinear measures, compressibility in particular, may be useful in improving labor prediction as a complement to other parameters [ 37 ]. Additionally, PhEn could be incorporated into the current research of pattern recognition [ 38 ] of EHG data or even be included in some fetal and maternal analysis software [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their exploratory analysis indicates that five main factors, possibly associated with vagal and cardiac sympathetic outflows, autonomic balance, homeostatic stability, and humoral effects, drive the complex heart rate dynamics. Heart-rate entropy analyses are also considered in the paper of Monteiro-Santos et al [ 8 ], who derived fetal heart rate series from cardiotocographic signals recorded on the mothers’ abdomen between 30 and 35 gestational weeks. Their results indicate that the complexity measures of fetal heart rate contribute to the prediction of labor, a finding that opens the possibility to improve the assessment and care of the fetus and the mother.…”
mentioning
confidence: 99%